The Art of Musical Improvisation on The Keyboard during the Italian Renaissance: Counterpoint Teaching According to Girolamo Diruta (1610) (Per Musi, 2018)
Fundamental part of the professional keyboardist practice in the Renaissance, musical improvisation is the relevant subject of Book II of the treatise Il Transilvano (1610). Published by Girolamo Diruta (? 1554 ‐1610), the Transylvanian exposes in 'Dialogue' the precepts of the art of music of his time and is Monumentum of its masters – Adriano Willaert, Gioseffo Zarlino and Claudio Merulo – active composers in the Most Serene Republic of Venice in sixteenth‐century. Priest of the Franciscan order and renowned organist of the cathedral churches of Chioggia and Gobbio, Diruta writes down the fortune of the Fantasia on the keyboard as the higher development of the study of Counterpoint. Based on the exposition of these principles, this article aims to contextualize the free ‐ but "right" ‐ manipulation of sounds according to that historical technique and offer an overview of Renaissance’s musical techniques.